Risk Factors of Non-Communicable Diseases Among Populations in Banat Area, Wad Medani City, Gezira State, Sudan 2013 - Ghebreselasie, Daniel Tekie; Elmukthar, Mohammed; Elsanousi, Salwa (Gezira Journal of Health Sciences, 2014)
The burden of non-communicable diseases is on the rise in middle and low income countries on top of the existing infectious diseases. In Sudan, non-communicable diseases account for a total of (44%) of all deaths. Moreover, the distribution of the specific risk factors are not systematically identified in the Gezira state, hampering the designing of appropriate preventive and control strategies. The objective of this study was to describe the distribution and prevalence of behavioral risk factors for non-communicable diseases. This cross sectional community based study was conducted in Banat area, Wad-Medani, Gezira State, Sudan, in May 2013. Data were collected using structured questionnaire. A total of 380 individuals over 40 years of age were selected for the study by simple random sampling technique. Data were analyzed using SPSS for Windows version (16.0). The distribution of the various categories of risk factors was identified. Among the behavioral risk factors, the prevalence of smoking for males and females were (25.8%) and (2.1%) respectively, alcohol consumption prevalence (1.1%), consumption of fruits and vegetables below adequate level (52.1.0%), low level physical activity (68.4%). All the risk factors were found more prevalent in males than females. This study showed Cigarette /tobacco use and physical inactivity were associated with personal history of NCDs and were found highly statistically significant (p-value <0.005). The study found, half (50%) of the study participants had family history of NCDs. Forty –two percent(42%) of study population had documented personal history of one of the NCDs, of which a combination of (DM+HTN) accounted for (12.6%) of cases followed by diabetes mellitus alone (11.1%). In conclusion, the magnitude of risk factors for noncommunicable diseases is considerably high in the study population. Appropriate preventive measure should be designed to prevent and control these risk factors